IgG4-related disease - Okazaki, Kazuichi, 1953- (Springer, 2017)
This volume focuses on IgG4-related disease (IgG4-RD), a novel clinical entity involving multiple organs and of unknown origin, associated with the abundant infiltration of IgG4-positive cells. It consists of nine chapters written by prominent experts in the field and discusses the disease concept, diagnosis and treatment, as well as recent findings on its pathogenesis and pathophysiology. As such, it offers an invaluable source of information for researchers and clinicians alike.
Keywords: Autoimmune diseases.; Immunoglobulin G.; Kidneys -- Diseases.; Pancreatitis.; elektronické knihy; electronic books